2021
DOI: 10.1007/s10452-021-09834-9
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics and freshwater microalgae: what do we know so far?

Abstract: The constant entry of microplastics in several environmental matrices has been of great concern to the scientific community and to society in general, mainly due to the mysteries that surround the implications of this pollutant in the environment. Freshwater ecosystems are resources especially susceptible to variations in environmental quality, and the lack of data on the impacts caused by plastic fragments exacerbates the vulnerability of this environment. Considering the results of other studies, which demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Adverse effects of microplastics towards microalgae may either stem directly from the physical presence of particles or by the secondary effects from leaching chemicals [ 3 , 4 ]; however, these are difficult to distinguish due to their frequent co-occurrence. The first process may lead to particle adsorption, aggregation, loss of membrane integrity, or shading effects as discussed in previous studies [ 2 , 5 , 6 ]. In contrast, the second process of indirect effects induced by chemicals leaching from microplastics has gained little attention for microalgae so far, despite many algae being able to colonize on plastic surfaces [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adverse effects of microplastics towards microalgae may either stem directly from the physical presence of particles or by the secondary effects from leaching chemicals [ 3 , 4 ]; however, these are difficult to distinguish due to their frequent co-occurrence. The first process may lead to particle adsorption, aggregation, loss of membrane integrity, or shading effects as discussed in previous studies [ 2 , 5 , 6 ]. In contrast, the second process of indirect effects induced by chemicals leaching from microplastics has gained little attention for microalgae so far, despite many algae being able to colonize on plastic surfaces [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…32 The previous ndings corroborated the toxicity results presented here, showing that microplastics reduce growth rates regardless of size, concentration, or type. 33,34 Based on the ndings of this study, it is possible to hypothesize the mechanism by which nTiO 2 is toxic to Scenedesmus obliquus. Previous studies on nTiO 2 toxicity towards Scenedesmus obliquus also showed similar results.…”
Section: Evaluation Of Cell Viabilitymentioning
confidence: 94%
“…In addition to Chl a, a variety of photosynthetic pigments such as Chl b and carotenoids also exist on chloroplast membrane, all of which are involved in absorbing light energy for photosynthesis [17,42]. The contents of these photosynthetic pigments in microalgae may be affected by MP [43], such as Chl b and carotenoids were more sensitive to polystyrene MP than Chl a in freshwater microalgae Euglena gracilis [17]. Moreover, the strain of A. pacificum ATHK is a PST-producing dinoflagellate, and the increase in Chl a content may also be related to PST biosynthesis in microalgal cells.…”
Section: Chlorophyll Amentioning
confidence: 99%
“…The extraction of PST from microalgal cells was according to our previous study [43]. In brief, 50 mL of microalgal cultures were centrifuged at 6000× g for 10 min to remove the supernatant, then pellets of microalgae were suspended in 2 mL of 0.1 mol L −1 acetic acid and vortex mixed for 1 min.…”
Section: Toxin Extractionmentioning
confidence: 99%